Impacto dos valores sociais na manutenção da violência de gênero. Vitória (2016) - Nespoli, Rafael Azevedo (2023)
Gender violence is the cruelest face of patriarchy, which is nourished by a constant construction and maintenance of values referring to attributes destined to men and women, reputed as natural, although arbitrary and historically constructed. Violence is presented as a naturalized mechanism, extracted from a series of values related to men, which together form the concept of honor. Research on the subject has shown that the state of Espírito Santo is one of the most prominent states in terms of violence against women, as is Vitória, its capital, which also has alarming numbers.This work seeks to investigate how violence is maintained as a valid resource in the solution of conflicts in gender relations, despite the discourses and protective public policies aimed at women. It is intended to demonstrate that men and women would still be conditioned to seek their appreciation in the adequate performance of social roles, in an approach of social representation constituted from the biological, which would offer them an apparent guarantee of belonging to a certain restricted group and, thus, share the privileges of that group. Belonging would be more relevant than the possibilities of insurgency, a circumstance that would prevent the decrease or even the end of violence. For this purpose, the police reports registered at the Police Station Specialized in Assistance to Women in the city of Vitória are used as a primary source, in particular the reports of the victims, in the year 2016. The choice of a single year is deliberate and intends to show that in this restricted period of time it is already possible to perceive how values are determinant in the perpetuation of violence.